Autoantibodies Against Serotoninergic 5-HT4 Receptor in Patients with Heart Failure - Breidert, M.; Wördehoff, S.; Hansen, A.; Eftekhari, P. (Hormone and Metabolic Research, 2012)
Serotoninergic 5-HT4 receptors have been detected in several tissues including the heart. An autoimmune mechanism may underline the pathogenesis of heart failure. The aim of this work was to look for autoantibodies to the 5-HT4 receptor in patients with heart failure. We looked for the presence of autoantibodies against 5-HT4 receptor as well as angiotensin II type (AT1), β1-adrenoceptor, and muscarinic M2 receptors in the sera of 176 patients with heart failure (female: n=96, male: n=80) and in 108 controls (female: n=69; male: n=39). The prevalence of 5-HT4 receptor autoantibodies was 18.8% (n=33) in the group of patients with heart failure and 4.6% (n=5) in the control group (p<0.002). The prevalence of autoantibodies against AT1 was 1.7 (n=3), β1-adrenoreceptor 0.6 (n=1), and muscarinic-receptor M2 4.2 (n=5). Female patients with diabetes and heart failure had a positive trend (p=0.07) to the presence of 5-HT4 receptor autoantibodies. In the group of female heart failure patients we found a significant correlation with the presence of coronary heart disease (p=0.05). The clinical relevance of 5-HT4 receptor autoantibodies has to be further studied. The prevalence of 5-HT4 receptor autoantibodies was highly significant in patients with chronic heart failure. It was also a significant correlation between these autoantibodies and the female subgroup with coronary heart disease. It is conceivable that the increased prevalence of autoantibodies against the 5-HT4 receptor in patients with heart failure is more than just an epiphenomenon.
Keywords: autoantobodies; diabetes mellitus type 2; heart failure; serotonin